2020
DOI: 10.3390/ani10122218
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Microsporidia in Wild Lagomorphs in Southern Spain

Abstract: Microsporidia are obligate intracellular protist-like fungal pathogens that infect a broad range of animal species, including humans. This study aimed to assess the presence of zoonotic microsporidia (Enterocytozoon bieneusi, Encephalitozoon intestinalis, Encephalitozoon hellem, and Encephalitozoon cuniculi) in organ meats of European wild rabbit (Oryctolagus cuniculus) and Iberian hare (Lepus granatensis) consumed by humans in Spain. Between July 2015 and December 2018, kidney samples from 383 wild rabbits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Regarding animal hosts, Blastocystis sp. and E. bieneusi have been reported in livestock (pigs) [ 30 ], pets (dogs, cats) [ 31 ], and captive non-human primates [ 32 ] and animal populations and wildlife (leporids, carnivores) [ 33 , 34 ]. In contrast, only a single microscopy-based survey has investigated the presence of Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding animal hosts, Blastocystis sp. and E. bieneusi have been reported in livestock (pigs) [ 30 ], pets (dogs, cats) [ 31 ], and captive non-human primates [ 32 ] and animal populations and wildlife (leporids, carnivores) [ 33 , 34 ]. In contrast, only a single microscopy-based survey has investigated the presence of Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…This study represents the first molecular‐based description of E. bieneusi in wild micromammals in Spain. Previous surveys in the country have identified these microsporidia at variable occurrence rates in wildlife, including mesocarnivores, pigeons, rabbits and wild boars (Dashti et al., 2020; Galván‐Díaz et al., 2014; Haro et al., 2005, 2006; Martínez‐Padilla et al., 2020; Santín et al., 2018); farmed animals, including cattle, goats, ostriches, pigs and rabbits (Abarca et al., 2021; Dashti et al., 2022; Galván‐Díaz et al., 2014; Lores et al., 2002) and companion animals, such as cats and dogs (Dashti et al., 2019; Galván‐Díaz et al., 2014; Lores et al., 2002). Genotype Peru11 was detected in three black rats from southern Spain.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, information on the occurrence and molecular diversity of E. bieneusi in wildlife is limited. Recent studies have identified this microsporidian species in wild boars and Iberian pigs sharing the same habitat, 38 wild and domestic carnivores, 54 -56 lagomorphs, 57 urban pigeons, 58 , 59 and wild micromammals. 60 In our study, E. bieneusi was identified in 10.4 and 0.8% of the investigated red deer and wild boar populations, respectively.…”
Section: Discussionmentioning
confidence: 99%